Testing for homologies in the axial skeleton of primitive echinoderms. (20th February 2017) - Paul, Christopher R. C.
Abstract: The extraxial axial theory is used to investigate homology of ambulacral and oral plating because it predicts terminal branching and terminal addition of plates in the axial skeleton, although exceptions to the former may occur in some Paleozoic echinoderms. The variety of morphological designs and anomalous individuals also provide tests of plate homology. Homology of ambulacra is generally accepted, with the hydropore and/or single gonopore in Carpenter's CD interray. In the 2-1-2 ambulacral pattern the unbranched ambulacrum is always in Carpenter's A ray. All ambulacral morphology requires just three instructions: 'grow, ' 'branch, ' and 'stop.' The range of variation in echinoderms with fewer than five ambulacra implies that both the 'branch' and 'stop' instructions acted independently in all five rays. Numbers of ambulacra may or may not correlate with numbers of orals. Two basic patterns of 'cystoid' oral plating occur; with a single radial (circum-oral, CO) plate from each ambulacrum plus a sixth in the CD interray, and with all six interradial peri-oral (PO) plates, with two in the CD interambulacrum. Five 'orals' may involve loss of PO3 or PO6. Erect ambulacral structures are lost first in taphonomy and so poorly known. All ambulacral skeletal elements bear the same topological relationship to ambulacral soft tissues. Where branched ambulacra occur, the trunk or flooring plates are often modified first brachiolars or pinnulars. Both brachioles and pinnules may arise from facets developed on one or two flooring plates. Terminal addition of plates, spacing of brachioles/pinnules, and lack of musculature to open cover plates all suggest that 'cystoids' had extensions of the water vascular system in their ambulacra.